Effects of a mindfulness based behavioral intervention for young adults with childhood maltreatment history on hippocampal morphometry: a pilot MRI study with voxel-based morphometry. (30th July 2020) - Joss, Diane; Lazar, Sara W.; Teicher, Martin H.
Highlights: Mindfulness based intervention for young adults with childhood maltreatment history Increased gray matter volumes at the right hippocampus in the mindfulness group Hippocampal changes negatively associated with depression and stress level changes in the mindfulness group Hippocampal changes positively associated with improvement in performance accuracy on an episodic memory task in the mindfulness group Abstract: Childhood maltreatment has long lasting impacts on neural development of the hippocampus, which is important for learning and memory. The present study aimed to assess the effects of a mindfulness based intervention on hippocampal morphometry and episodic memory in this population. We administered MRI, psychological questionnaires and an episodic memory task to 21 participants (5 males) before and after a mindfulness-based behavioral intervention, compared to 21 participants (7 males) on the waiting list. Changes in G ray M atter V olume (GMV) in bilateral hippocampi were analyzed with V oxel-B ased M orphometry (VBM). One cluster was identified in the right hippocampus with a group by time interaction effect that consisted of 130 contiguous voxels but fell short of significance with full FDR correction ( p  = 0.077). GMV in this cluster increased by 0.76% in the mindfulness group and decreased by 0.78% in the control group. Within the mindfulness group, changes in hippocampal GMV were negatively associated with changes in perceived stress and depression severity and positively associated with enhancement in performance accuracy on the episodic memory task. Findings from this pilot study suggest that a mindfulness-based intervention may lead to an increase in partial hippocampal GMV with associated symptom reduction and improvement in episodic memory.